PENGARUH KELOMPOK TEMAN SEBAYA DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN KEWIRAUSAHAAN - Krisnamukti Pangestu Wahyu Putra (JURNAL ILMIAH EDUNOMIKA, 2024)
The research aims to know: 1) the influence of peer group’s on entrepreneurial learning outcomes student students of class XII Automation and Office Administartion at SMK Negeri 1 Sragen in the academic year 2021/2022; 2) the influence of independence of student learning on entrepreneurial learning outcomes student of class XII Automation and Office Administration at SMK Negeri 1 Sragen in the academic year 2021/2022; 3) the influence of peer group’s and independence of student learning on entrepreneurial learning outcomes students of class XII Automation and Office Administration at SMK Negeri 1 Sragen in the academic year 2021/2022. This research used quantitative research with a correlational research design. The result of research showed that 1) there was a significant positive effect of peer group’s on learning achievement on entrepreneurship proved tcount>ttable (5,680 > 1,99006); 2) there was a significant positive effect of self-motivated learning on learning achievement on entrepreneurship proved tcount>ttable (9,413 > 1,99006); 3) there was a significant positive effect of peer group’s and self-motivated learning on learning achievement on entrepreneurship proved Fcount>Ftable (228,879 > 3,11). This result of research showed the amount of effective contribution toghether equal to 85,2% and the rest still 14,8% which effected by other variables. Keywords : Peer Group’s, Independence of Student Learning and Entrepreneurship Learning outcomes.